The Effect of Quality of Life on Medication Compliance Among Dialysis Patients - Nagasawa, Hiroyuki; Tachi, Tomoya; Sugita, Ikuto; Esaki, Hiroki; Yoshida, Aki; Kanematsu, Yuta; Noguchi, Yoshihiro; Kobayashi, Yukio; Ichikawa, Etsuko; Tsuchiya, Teruo; Teramachi, Hitomi (Frontiers in Pharmacology, 2018)
Dialysis treatment is known to lead to reduced quality of life (QOL) among patients. This decreased QOL is believed to influence medication compliance, although this effect has not yet been clarified. In this study, we investigated whether decreased QOL due to dialysis treatment does in fact influence medication compliance. Participants were 92 patients who self-managed their medication and were receiving dialysis treatment at Secomedic Hospital or Chiba Central Medical Center. We surveyed their age, sex, dialysis period, and medication management situation, and administered the EQ-5D and Kidney Disease Quality of Life Instrument–Short Form. A multiple logistic regression analysis with medication compliance as the dependent variable and QOL as the independent variable was conducted. The recovery rate and effective response rate were both 100%. The results indicated that patients with good sleep QOL (mean or above) had higher odds of medication compliance (odds ratio, 3.36; 95% confidence interval, 1.26-8.96; P = 0.016). Therefore, improving the quality of sleep of dialysis patients might help to improve their medication compliance.